Does Rosie Like Riveting? Male and Female Occupational Choices. (16th September 2021) - Lordan, Grace; Pischke, Jörn‐Steffen
Abstract : Occupational segregation and pay gaps by gender remain large, while many of the constraints traditionally believed to be responsible for these gaps seem to have weakened over time. We explore the possibility that women and men have different tastes for the content of the work that they do. We relate job satisfaction and job mobility to measures that proxy for the content of the work in an occupation, which we label 'people', 'brains' and 'brawn'. The results suggest that women value jobs high on 'people' content and low on 'brawn'. Men care about job content in a similar fashion, but have much weaker preferences. High school students show similar preferences in a discrete choice experiment and indicate that they make their choices based mainly on preferences for the work itself. We argue that the more pronounced preferences of women can account for occupational sorting, which often leads them into careers with large pay penalties for interruptions due to childbearing.